IBM FABRIC MASK MAKING TRAINING FOR THE RESIDENTS OF EAST PENFUI VILLAGE, KUPANG TENGAH, KUPANG DISTRICT IN CENTRAL PANDEMI COVID-19 - Anita Lidesna Shinta Amat; Herman Pieter Louis Wungouw; Efrisca Damanik (UNUSA Press, 2021)
Covid-19 pandemic has become a global problem that has an impact on almost all levels of society, both those with income and no income. Recommendations regarding the use of masks in the community, during home care, and in health care facilities in areas need to be mobilized massively. Current information indicates that the two main modes of transmission of the COVID-19 virus are respiratory droplets and contact. The use of masks has become a culture in life and daily activities so that the need for masks has increased. Therefore, it is necessary to have a stock of masks that are clean and of good type of cloth as prevention and first aid when doing activities outside the home. The condition of the residents in Penfui Village shows that not all are able to provide a large stock of masks for at least 1 house / small family. This situation prompted the Community Service team from the Faculty of Medicine (FK) Undana to provide training in making cloth masks for the community in East Penfui Village.